Navigating Sexuality and HIV/AIDS: insights and foresights of Zimbabwean adolescents - Gudyanga, Ephias; Moyo, Sarah; Gudyanga, Anna (SCIENCEDOMAIN International, 2016)
The study navigated insights and foresights of adolescents towards sexuality and HIV/AIDS, premised on Zimbabwean context. 147 secondary school learners (72 females, 75 males, age range 13-20 years) were the randomly sampled participants. Questionnaires based on a 5 point Likert scale written on a continuum of SA-SD and focus group interviews were the main data generating tools. It was found that adolescents are well informed on issues relating to sexuality and HIV/AIDS; however this knowledge was not reflected in their behaviour. Irresponsible sexual behaviour is noted through the information that the adolescents gave. A large number (47.7%) of the adolescents have had sex, 32% of them without any protection, 11% with prostitutes and 2.1% with older people. Participants regarded the school as giving the most reliable information on HIV/AIDS. However, it was revealed that the school was found wanting pertaining to educating adolescents on sexuality and HIV/AIDS. Guidance and Counselling lessons were noted to be few and erratic, in some instances the lessons were not given at all. It was concluded that the learners need more education on sexuality and HIV/AIDS that also includes issues regarding attitudes and behavioural change. Methods and techniques of learning HIV/ AIDS by learners must be changed to a more lucrative visual participatory approach.